A multicomponent tetrazolo indole synthesis. Issue 54 (15th June 2021) - Lei, Xiaofang; Lampiri, Panagiota; Patil, Pravin; Angeli, Giasemi; Neochoritis, Constantinos G.; Dömling, Alexander
Abstract : A short, diverse, and scalable Ugi synthesis towards the bioactive tetrazolo indoles. Abstract : The ubiquitous presence of the indole fragment in natural products and drugs asks for ever novel syntheses. We report an unprecedented mild, two-step synthesis of 2-tetrazolo substituted indoles based on the Ugi-tetrazole reaction combined with an acidic ring closure. A gram-scale synthesis, a bioactive compound and further transformations were performed.